Case series: Inflammatory myofibroblastic bladder tumor in regional Australia. (May 2021) - Cresser, Sam; Nzenza, Tatenda; Tripathy, Sagarika; Hall, Rohan
Abstract: Introduction and importance: Inflammatory myofibroblastic tumor (IMT) is a rare tumor subtype that affects multiple organ systems. This case series adds a regional perspective to the literature, demonstrating rare urological cancers can be managed excellently in regional settings. Case presentation: We report a case series of two patients in regional Australia who were diagnosed with IMT of the urinary bladder. Both patients received computed tomography (CT) and ultrasound (US) imaging to investigate lower urinary tract symptoms (LUTS). Following initial diagnosis of a bladder tumor, both patients underwent surgery, one having a transurethral resection of bladder tumor (TURBT) with the other receiving a partial cystectomy. Histology from both surgeries revealed IMT of the urinary bladder, with the first case going on to receive a partial cystectomy to ensure clear surgical margins. Both patients recovered well post-operatively, with CT cystograms revealing water-tight bladders. Initial follow up reveals no recurrence of disease. Clinical discussion: IMT of the urinary bladder is an exceedingly rare clinical entity which is fortunately benign and can be well managed with appropriate surgical intervention. Conclusion: IMT can be well managed in regional hospitals equipped with appropriate surgical, pathological and oncological services. Highlights: Urinary IMT is a rare clinical entity, characterised by three histological patterns. Complete surgical resection is gold standard management. Rare cancers can be managed in regional settings with appropriate multidisciplinary input. Regional patients appreciate the support and financial ease of local care.